2020
DOI: 10.1017/s0047404520000640
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic variation and change in the Cockney Diaspora: The role of place, gender, and identity

Abstract: Recent research has suggested that two linguistic processes are displacing Cockney: the emergence of Multicultural London English (MLE) in inner London and dialect levelling (e.g. Kerswill & Williams 2005). This study investigates firstly whether Cockney phonetic features have ‘moved East’ to Essex (Fox 2015), and secondly the features’ indexicality in relation to place and identity. Fifty-four participants from Debden, an outpost of the Cockney Diaspora, completed a sociolinguistic interview. Vowel measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…As Debden was originally inhabited almost exclusively by East Londoners, it seems probable that Debden speakers will use consonantal features that have previously been reported in Cockney. This is in line with previous research that found that, despite some apparent-time change toward Standard Southern British English variants, a Cockney vowel system was brought to Debden along with the Cockneys who relocated (Cole, 2020; Cole & Evans, 2020; Cole & Strycharczuk, 2019). Nonetheless, this paper does not have the scope to provide detailed descriptions of the variety of English spoken in Debden 1 .…”
Section: Community Of Interestsupporting
confidence: 91%
See 4 more Smart Citations
“…As Debden was originally inhabited almost exclusively by East Londoners, it seems probable that Debden speakers will use consonantal features that have previously been reported in Cockney. This is in line with previous research that found that, despite some apparent-time change toward Standard Southern British English variants, a Cockney vowel system was brought to Debden along with the Cockneys who relocated (Cole, 2020; Cole & Evans, 2020; Cole & Strycharczuk, 2019). Nonetheless, this paper does not have the scope to provide detailed descriptions of the variety of English spoken in Debden 1 .…”
Section: Community Of Interestsupporting
confidence: 91%
“…The speakers took part in a sociolinguistic interview, consisting of reading a wordlist and passage as well as an open interview with myself, a native Debden speaker. The production data for this paper is extracted from the open interviews (see Cole & Evans [2020] or Cole & Strycharzuk [2019] for phonetic analyses of wordlist and passage data). The interviews consisted of semistructured conversations about a range of topics with a focus on the participants’ lives, views on the local area, experiences living in Debden, sense of identity, and the linguistic features found in Debden.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations